The Place of Invisible Religion and New Media Folklore in the Social Construction of Reality - Kajfosz, Jan (Literatura Ludowa. Journal of Folklore and Popular Culture, 2025)
The aim of this paper is to identify the point of convergence between folklore and religious practices through the lens of phenomenology and social constructivism. The author interprets contemporary verbal folklore as a form of invisible religion that fosters community through conceptual frameworks, symbolic universes, social norms, and patterns of perception and action. Folklore and religion exhibit several shared characteristics: 1. both phenomena serve a sociointegrative function; 2. both phenomena evolve in form and content over time; 3. both phenomena evoke intense ambivalent emotions; 4. both eligious and aesthetic experiences elicited by folklore texts are characterized by a fusion of planes of representation (merging of an object and its sign); 5. both phenomena possess a pragmatic dimension shaping social attitudes and inspire their earers to action.